Fitz-Hugh–Curtis Syndrome in an Adolescent Athlete: MRI Diagnosis of an Atypical Presentation: Fitz-Hugh–Curtisov sindrom pri adolescentki: zapoznela diagnoza subtilne klinične slike - Čokolič, Eva; Lučič Šrajer, Lucijan; Kodrič, Ivana; Dobnik, Sarah; Žerdin, Matija; Sefić Pašič, Irmina (Acta Medico-Biotechnica, 2025)
Purpose: To emphasize the diagnostic role of magnetic resonance imaging (MRI) in identifying Fitz-Hugh–Curtis syndrome (FHCS) in an adolescent patient with a subtle clinical presentation. Methods: A 17-year-old female presented with acute onset right upper quadrant and right shoulder pain. The initial diagnostic workup, including ultrasound (US), computed tomography (CT), and laboratory testing was inconclusive. Due to persistent symptoms and elevated inflammatory markers, MRI of the abdomen and pelvis was subsequently performed. Results: MRI demonstrated a bilateral pyosalpinx with restricted diffusion, free fluid in the pelvis and subhepatic region, and linear adhesions between the hepatic capsule and peritoneum, which was consistent with pelvic inflammatory disease (PID) complicated by FHCS. Microbiologic analysis confirmed a Chlamydia trachomatis infection. The patient received targeted antibiotic therapy with clinical improvement. Conclusion: FHCS represents a rare but important complication of PID that may present with non-specific or extra-pelvic symptoms. MRI is the modality of choice for confirming PID-related complications and perihepatic inflammation, offering high sensitivity and the advantage of radiation-free imaging, which is especially relevant in the adolescent population.